Multidisciplinary management for the treatment of proximal posterior inferior cerebellar artery aneurysms. (4th May 2017) - Cho, Kwang-Chun; Kim, Yong Bae; Suh, Sang Hyun; Joo, Jin Yang; Hong, Chang-Ki
Abstract: Objectives : Aneurysms of the proximal posterior inferior cerebellar artery (PICA) are rare. The management of proximal PICA aneurysms is challenging with either surgical or endovascular treatment. We report our successful experience of treating PICA aneurysms with a multimodal approach. Methods : Of 2382 treated aneurysms, 22 aneurysms in 21 patients (male:female 8:13, mean age 48.9 years) were enrolled from March 1998 to December 2015. We treated the aneurysms with a multimodal approach and performed angiography to examine aneurysm regrowth at the 12 months follow-up. Clinical outcomes were evaluated based on the modified Rankin Score (mRS) at the time of discharge and 12 months postoperatively. The treatment modality was mainly dependent on the character of the aneurysms and the clinical presentation of the patients. Results : Microsurgery was performed in seven patients, which entailed proximal occlusion with distal revascularization in two and microsurgical clipping in five. Endovascular treatment was performed in 10 patients because of a serious medical condition, or vertebral artery (VA)/ or PICA tortuosity. Four were treated with coil embolization and six with stent or balloon-assisted coil embolization. Combined surgical and endovascular treatment was applied in four patients. They were treated with distal revascularization followed by occlusion with coils of the aneurysm-incorporated PICA. All patients achieved complete cure of the PICA aneurysms without complications except for one case of cerebrospinal fluid (CSF) leakage. Discussion : Endovascular and microvascular neurosurgeons should work closely in managing these challenging problems. Neurosurgeons should consider multimodal treatment in these cases including trapping after occipital artery (OA)-PICA bypass.